STR analysis of human DNA recovered from bathwater and other water samples for forensic identification - Mitsuyo Machida; Kazuhiko Kibayashi (PLoS ONE, 2026)
Human DNA is widely distributed in the environment and can be released into water through skin cells, sweat, and other biological materials. In forensic investigations involving drowning or suspected immersion events, bathwater represents an underexplored but potentially informative source of DNA evidence. This study evaluated the feasibility of recovering and analyzing human DNA from bathwater for short tandem repeat (STR) profiling. Bathwater samples were collected from 11 volunteers after 1, 2, 5, and 10 minutes of immersion, as well as from 12 forensic autopsy cases. DNA was concentrated using a filtration-based method and analyzed for DNA quantity, degradation, and STR profiling success. Both DNA yield and integrity generally increased with immersion duration, and most samples yielded complete STR profiles after 10 minutes. Considerable interindividual variation in DNA shedding was observed, and residual DNA from prior bath users frequently contributed to mixed profiles. Allele drop-ins were common in low-template or mixed samples but decreased as DNA quantity increased. STR profiles were successfully recovered from indoor samples (e.g., bathtubs), whereas no interpretable profiles were obtained in the limited number of outdoor cases examined in this study. These findings demonstrate that bathwater may serve as a useful supplementary source of human DNA in forensic investigations, particularly in indoor drowning cases. Although mixed profiles necessitate cautious interpretation, DNA recovered even after brief immersion may support victim identification or contribute to assessments of potential co-presence in conjunction with other evidence. Overall, this study suggests that bathwater represents a supplementary and context-dependent source of human DNA for forensic analysis in aquatic settings.